Peran Edukasi dan Pelatihan Kemasan Dalam Dalam Meningkatkan Kualitas Usaha Mikro, Kecil dan Menengah (UMKM) - Silvia, Deli; Prastiwinarti, Wiwi; Muryeti; Ningtyas, Rina; Imam, Saeful (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2023)
One of the problems often faced by SME entrepreneurs is the lack of knowledge about the right type of material to use according to the product they have and the design and composition of labels according to applicable regulations. Packaging designs and labels become icons that can make these products competitive and attract more consumers. So that the main goal of SME entrepreneurs is achieved, namely increasing turnover. Among them, P-IRT/MD permits, halal certificates, product composition, serving sizes, serving suggestions, and storage suggestions, so that consumer safety in consuming these products can run well. Dapoer Ikan partners Umi Ali and Rendang Bu Guru are SMEs that do not yet have a P-IRT permit and labels that do not comply with food packaging regulations. The knowledge that is still minimal about this is the background for the TICK Study Program to carry out community-based science and technology services regarding improving the quality of packaging for the UKM Dapoer Ikan Umi Ali and Rendang Bu Guru through socialization and training. The implementation of the service is carried out through offline educational seminars and training regarding 1) Packaging design for SMEs that sell; 2) Appropriate material selection and 3) Appropriate SME packaging regulations. This activity aims to make partners able to compete better by having packaging that is in accordance with regulations and attractive label designs and the TICK Study Program can apply their knowledge to Dapoer Ikan Partners Umi Ali and Rendang Bu Guru. The results of the evaluation of participants' activities became more knowledgeable about the world of packaging and all participants agreed to hold seminars and training activities like this on a regular and continuous basis so that packaging, product quality, and product sales turnover increased.   Salah satu diantara permasalahan yang sering dihadapi oleh pengusaha UKM adalah keterbatasan ilmu mengenai jenis material yang tepat digunakan sesuai produk yang dimiliki serta desain dan komposisi label sesuai regulasi yang berlaku. Desain dan label kemasan menjadi ikon yang dapat menjadikan produk tersebut memiliki daya saing dan lebih menarik minat konsumen. Sehingga tujuan utama dari pengusaha UKM tercapai yaitu omzet meningkat. Diantaranya, izin P-IRT/MD, Serifikat halal, komposisi dari produk, takaran saji, saran penyajian, hingga saran penyimpanan, agar keamanan konsumen dalam mengkonsumsi produk tersebut dapat berjalan dengan baik. Mitra Dapoer Ikan Umi Ali dan Rendang Bu Guru merupakan UKM yang belum memiliki izin P-IRT dan label yang belum sesuai dengan regulasi kemasan pangan. Pengetahuan yang masih minim mengenai hal ini, menjadi latar belakang Prodi TICK melaksanakan pengabdian IPTEK berbasis Masyarakat mengenai peningkatan kualitas kemasan UKM Dapoer Ikan Umi Ali dan Rendang Bu Guru melalui sosialisasi dan pelatihan. Pelaksanaan pengabdian dilakukan melalui seminar edukasi dan pelatihan secara offline mengenai 1) Desain kemasan UKM yang menjual; 2) Pemilihan material yang tepat dan 3) Regulasi kemasan UKM yang sesuai. Kegiatan ini bertujuan agar mitra mampu bersaing lebih baik dengan memiliki kemasan yang sesuai dengan regulasi dan desain label yang menarik dan Prodi TICK dapat mengaplikasikan ilmu yang dimiliki kepada Mitra Dapoer Ikan Umi Ali dan Rendang Bu Guru. Hasil evaluasi kegiatan peserta menjadi bertambah wawasan mengenai dunia kemasan dan semua peserta setuju diadakan kegiatan seminar dan pelatihan seperti ini secara berkala dan berkesinambungan agar kemasan, kualitas produk dan omzet penjualan produk meningkat.